Variasi produk, label halal, kualitas layanan, dan harga: faktor pendorong pembelian ulang oleh generasi Z dalam industri makanan cepat saji - Rohmawati, Nur Aeni; Anwar, Aan Zainul (Journal of Management and Digital Business, 2025)
The fast-food industry is experiencing rapid growth among Generation Z, where factors such as product variety, halal labeling, service quality, and price play an important role in shaping repeat purchase decisions and customer loyalty. Understanding these factors is key for businesses to design more effective marketing strategies. This study focuses on Gacoan Noodle restaurants in Central Java and aims to analyze the influence of product variety, halal labels, service quality, and price on Generation Z's repurchase decision. A quantitative approach was used in this study, and questionnaires were distributed to 100 respondents using random sampling techniques. The data obtained was analyzed using multiple linear regression. The results show that product variety, service quality, and price have a positive and significant influence on repurchase decisions, while the halal label shows a negative and significant impact. Among all variables, product variety is the most dominant factor in driving repurchase decisions. Overall, the four variables simultaneously influence Generation Z’s repurchase decision in the fast-food industry.